Para atleta para sa bansa a campaign featuring national para athletes to raise awareness and financial support in the Philippines - Siao, Patricia Elise G.; Reyes, Mitzi Marie Aguilar (Quezon City College of Fine Arts, University of the Philippines Diliman, 2019)
Para athletes is the term used to refer to Persons with Disabilities(PWD) athletes. Filipino para athletes are among the most gifted athletic groups in the country. They train and compete in the fields of athletics, swimming, powerlifting, wheelchair basketball, table tennis, and chess, among others. Our para athletes are excelling and reaping medals in the international scene. Among the highly recognized Filipino para athletes is Adeline Dumapong-Ancheta, the first Filipino Paralympic Games medalist who won a bronze for powerlifting in the 2000 Sydney Summer Paralympic Games. Josephine Medina, a polio victim, won a bronze medal for table tennis in the 2016 Rio Paralympic Games. Andy Avellana, a limb amputee, has won in various international international athletic events like long jump, high jump, and triathlon. Another swimmer, Erinie Gawilan who was born with congenital limb defects, won the first gold medal for the Philippines in the 2018 Asian Para Games. According to the 2010 census of the Philippines Statistics Authority, there are about 1.4 million PWDs in the Philippines. Out of this population, Mr. Francis Diaz, the secretary general of the Philippine Paralympic Committee, says merely 140 are in the national training pool of para athletes. Our para athletes are few, but they are doing very well. The recent achievements in international competitions, the earliest being Dumapong-Ancheta's bronze in 2000, show that involvement PWDs in sports is only gaining attention and support lately. However, the para athletes still lack funding, promotion, recognition, and attention. Two para athletes from the Philippines Paralympic swimming team, both of which have already spent two years in the national training pool, have yet to receive allowance; national team para athletes are entitled to receive an allowance of at least Php15,000 monthly. The Warriors Wheelchair Basketball Team in the Philippines are currently using wheelchairs that weigh up to 20 kilograms while their international competitors use equipment weighing only 8-9 kilograms. Despite that challenge, the team was still able to win second runner-up in the 2017 ASEAN Para Games. To address theses problems, this project aims to gain attention from the government and private companies to support and sponsor PWD athleticism through a campaign featuring successful para athletes. The campaign is geared towards rallying financial support for para athletes, as well as inspiring involvement of Filipino PWDs into sports. The ultimate goal of this project is to contribute in uplifting the lives of Filipino para athletes.
Thesis (Bachelor of Fine Arts in Visual Communication)--University of the Philippines Diliman
Bibliography : leaves 175-176.
Keywords: Sports for people with disabilities -- Philippines